1999
DOI: 10.1007/bf03218030
|View full text |Cite
|
Sign up to set email alerts
|

Extended resection for lung cancer invading mediastinal organs

Abstract: We analyzed 49 patients with non-small-cell lung cancer invading mediastinal organs such as the left atrium (15), superior vena cava (13), trachea (11), aorta (5), thoracic vertebral body (4) and esophagus (1). Lung resection included lobectomy (37), pneumonectomy (8) and limited resection (4). Twenty-seven patients underwent carina- or bronchoplasty. Complete resection was possible in 35 patients. Operative mortality was 12% and overall 5-year survival was 13%. Median survival time was 519 days. Factors signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…Our results on 5-year survival of patients with aorta invasion are in contrast to that reported in previous studies [7]. This should be attributed to the highly selected group of patients in our study [8][9][10][11][12][13]. Previous reports have shown that long-term survival is possible after limited resection of the aortic adventitia along with the primary tumor [7,9,12,[14][15][16].…”
Section: Discussioncontrasting
confidence: 85%
“…Our results on 5-year survival of patients with aorta invasion are in contrast to that reported in previous studies [7]. This should be attributed to the highly selected group of patients in our study [8][9][10][11][12][13]. Previous reports have shown that long-term survival is possible after limited resection of the aortic adventitia along with the primary tumor [7,9,12,[14][15][16].…”
Section: Discussioncontrasting
confidence: 85%
“…MRI may be useful to evaluate the extension of the tumor into the LA. In our experience, the rate of complete resection was 81.8%, which is in line with the rate reported by Doddoli et al 5 (86%), as well as those reported by Bobbio et al 6 (83%), Spaggiari et al 8 (80%), and Galvaing et al 12 (89.4%), and is certainly higher in respect to the R0 rate, around 20%, reported in series including patients treated in the pre CT scan era 21,22 and also in line with other more recent experiences. 9,10 However, in our experience, the group of patients with R0 disease had the best prognosis (55% at 5 years).…”
Section: Discussionsupporting
confidence: 89%
“…As regards morbidity, our data (36.4%) appear relatively high if compared with current figures in standard lobectomies, but one should consider that patients undergoing LA resection have an increased postoperative risk due to locally more advanced disease. Morbidity and mortality data reported in the literature are quite variable, ranging from 5 to 52.6%, [2][3][4][5][6][7][8][9][10][11][12][18][19][20][21][22] probably due to the heterogeneity of the studied population and perioperative treatments. We did not register any deaths either intraoperatively or postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival after left atrium resection was 22%. Takahashi et al [24] reported 53 cases of extended resection of mediastinal organs including left atrium (n = 15), superior vena cava (n = 13), and aorta (n = 5) showed a 5-year survival rate of 13% with 12% operative mortality. However, N0 or N1 cases showed a 36% 5-year survival rate.…”
Section: Heart and Great Vessel Invasionmentioning
confidence: 97%